CONSUMER PROTECTION LAW IN BUYING AND SELLING GOODS ONLINE - Syaparuddin (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2022)
In recent years, ICT growth has accelerated at a remarkable rate. Sellers (business actors) and purchasers (consumers) are no longer brought together during online transactions (buyers). These deals are made through electronic commerce (E-Commerce). The parties in electronic transactions, the buyers, are often affected by parties who violate agreements and agreements offered through e-commerce mechanisms, despite the fact that legislation regulating e-commerce have been developed. As a result, the purpose of this research is to identify the applicable consumer protection laws for e-commerce. Researcher adopts a normative strategy here. According to the study's findings, if a consumer or customer receives a product that does not match the description or image of the advertised product on the internet, the consumer can launch a civil complaint against the business actor or seller on the grounds of default or against the law. The Consumer Protection Act and the Information and Electronic Transactions Act are two pieces of legislation that protect consumers' rights. The government and society at large also have significant responsibilities in terms of consumer protection, particularly in the form of oversight.